Monitoring orangutan reintroduction: Results of activity budgets, diets, vertical use and associations during the first year post-release in Kehje Sewen Forest, East Kalimantan, Indonesia - FITRIAH BASALAMAH; SRI SUCI UTAMI ATMOKO; DYAH PERWITASARI-FARAJALLAH; IBNUL QAYIM; JAMARTIN SIHITE; MARIA VAN NOORDWIJK; ERIK WILLEMS; CAREL P. VAN SCHAIK (Biodiversitas Journal of Biological Diversity, 2018)
Basalamah F, Utami-Atmoko SSU, Perwitasari-Farajallah D, Qayim I, Sihite J, Van Noordwijk M, Willems E, Van Schaik CP. 2018. Monitoring orangutan reintroduction: Results of activity budgets, diets, vertical use and associations during the first year post-release in Kehje Sewen Forest, East Kalimantan, Indonesia. Biodiversitas 19: 689-700. Pongo pygmaeus morio, a subspecies of orangutan founded east Kalimantan is steadily declining and classified as endangered. A reintroduction program was recently established. We monitored the reintroduced individuals during their first year post-release at Kehje Sewen Forest in East Kalimantan to document the adjustment to their new habitat. Here, we present a report on the activity patterns, food choice, travel height, nest-building abilities and associations of six individuals ranging between eight and thirteen years old. Our results show that all individuals survived their first year. They spent most of their time feeding and had a largely frugivorous diet, similar to wild orangutans. However, although they were able to build nests, they reused or rebuilt old nests more often than expected. They also spent 16% of their total activity time on the ground, more than expected. This information will contribute to attempts to evaluate factors affecting the adjustment process, and thus optimizing future reintroduction procedures.